Bioarchaeology and the Ethics of Research Using Human Skeletal Remains - DeWitte, Sharon N. (History compass, 2015)
In a recent article, Pobst refers to bioarchaeologists as "grave-robbing scientists," a phrase that negatively and inaccurately describes such researchers. This paper provides an overview of the history of the collection of human skeletal remains by anthropologists and others, which has resulted in misconceptions about current practices in the field, and of the important changes that have been made in recent decades to ensure that bioarchaeological research is done ethically. Recent Black Death research is emphasized as an example of bioarchaeology that conforms to the ethical standards of numerous organizations and avoids the exploitative use of human remains against the wishes of descendant populations.